Peran BMT Berkah Mandiri Dalam Pemberdayaan Ekonomi Anggota Melalui Pembiayaan Murabahah - Nicky Wahyudi (-, 2022)
Baitul Maal Wat Tamwil (BMT) is a micro-scale Islamic financial institution that uses a financing scheme, in the current modern era, micro-scale Islamic financial institutions have shown significant developments from time to time. So Baitul Maal Wat Tamwil is the choice because it applies the Maal and Tamwil schemes in one activity concept.This study aims to determine the role of BMT Berkah Mandiri in the economic empowerment of members and to determine the success of BMT Berkah Mandiri in an effort to release people's dependence on non-halal/usury practices. This research method uses a qualitative descriptive approach.The results of this study indicate that the presence of BMT Berkah Mandiri is an alternative for people who need financing with the sharia system in order to get justice and can be freed from bad habits, namely non-halal/rib transactions.